Chemosensory cues affect amygdaloid neurogenesis and alter behaviors in the socially monogamous prairie vole. (19th March 2014) - Liu, Y.; Lieberwirth, C.; Jia, X.; Curtis, J. T.; Meredith, M.; Wang, Z. X.
Abstract The current study examined the effects of pheromonal exposure on adult neurogenesis and revealed the role of the olfactory pathways on adult neurogenesis and behavior in the socially monogamous prairie vole (Microtus ochrogaster). Subjects were injected with a cell proliferation marker [5‐bromo‐2′‐deoxyuridine (BrdU)] and then exposed to their own soiled bedding or bedding soiled by a same‐ or opposite‐sex conspecific. Exposure to opposite‐sex bedding increased BrdU labeling in the amygdala (AMY), but not the dentate gyrus (DG), of female, but not male, voles, indicating a sex‐, stimulus‐, and brain region‐specific effect. The removal of the main olfactory bulbs or lesioning of the vomeronasal organ (VNOX) in females reduced BrdU labeling in the AMY and DG, and inhibited the male bedding‐induced BrdU labeling in the AMY, revealing the importance of an intact olfactory pathway for amygdaloid neurogenesis. VNOX increased anxiety‐like behavior and altered social preference, but it did not affect social recognition memory in female voles. VNOX also reduced the percentage of BrdU‐labeled cells that co‐expressed the neuronal marker TuJ1 in the AMY, but not the DG. Together, our data indicate the importance of the olfactory pathway in mediating brain plasticity in the limbic system as well as its role in behavior.